Polyploid and hybrid genomics - Chen, Z. Jeffrey; Birchler, James A. (Ames, Iowa : Wiley-Blackwell, 2013)
"A thorough synthesis of the genomic basis of polyploid and hybrid vigor"--Provided by publisher.
Machine generated contents note: Preface: Polyploidy and Hybridity Jim Birchler and Jeff Chen Section I Genomics of hybrids1. Yeast hybrids and polyploids as models in evolutionary studies Avi Levy 2. Transcriptome profiling of Drosophila interspecific hybrids: insights into mechanisms of regulatory divergence and hybrid dysfunction Jose Ranz & Carlos Machado 3. cis- and trans-regulation in Drosophila interspecific hybrids Patricia Wittkopp 4. Gene expression and heterosis in maize hybrids Mei Guo 5. Integrating "omics" data and expression QTLs to understand maize heterosis Patrick Schnable6.Genomics and heterosis in hexaploid wheat Qixin Sun & Zhingfu Ni 7. The progress of genomics and heterosis studies in hybrid rice Zhen Zhu 8. Heterosis: the case for single gene overdominance Zach Lippman Section II Genomics of polyploids 9. Genomics and transcriptomics of photosynthesis in polyploids Jeff Doyle & Jeremy Cote 10.Chromosomal and gene expression changes in Brassica allopolyploids Eric Jenczewski 11. Dynamics of duplicated gene expression in cotton Keith Adams & Jonathan Wendel 12. Reprogramming of gene expression in the genetically stable bread allohexaploid wheat Boulos Chalhoub13. Nucleo-cytoplasmic interaction (NCI) hypothesis of genome evolution and speciation in polyploid plants revisited: Polyploid species-specific chromosomal polymorphisms in wheat Bikram S. Gill & B. Friebe Section III Mechanisms for novelty in hybrids and polyploids 14. Genes causing post-zygotic hybrid incompatibility in plants: A window into coevolution Kirsten Bomblies 15. Meiosis in polyploids Graham Moore 16. Genomic imprinting: Parental control of gene expression in higher plants Charles Spillane 17. Seed development in interploidy hybrids Rod Scott 18. Chromatin and small RNA regulation of nucleolar dominance Pedro Nunes & Olga Pontes 19. Genetic rules of heterosis in plants Jim Birchler 20. Chromatin and gene expression mechanisms in hybrids Xin Wang Deng 21. Genetic and epigenetic mechanisms for allopolyploidy and hybridity Jeff Chen.
Includes bibliographical references and index.
Keywords: Polyploidy; Hybrid Vigor; Hybridization, Genetic